Application of Training and Development to Improve the Performance of Teachers at SMP 5 Medan after the Pandemic - Sebayang, Saimara; Wahyuni, Sri (Journal of Community Research and Service, 2022)
This Community Service activity aims to conduct training and development to improve teacher performance after the Covid-19 Pandemic. The location of service activities at the Negri 5 Junior High School (SMP) Medan.  This activity uses the blanded learning method which is a learning method which combines two learning patterns, namely by utilizing technology and learning through teaching staff.  This service activity went smoothly and all participants who were teachers were very enthusiastic in participating in the activity until it was completed. After the material was delivered, the participants were given the opportunity to ask questions and answers about the discussion of the material and even the obstacles experienced when learning was carried out after this Pandemic. There are 6 (six) models offered by the activity team that are considered capable of helping to improve Teacher performance, namely: 1) Using a Controlled Face-to-Face System Model. 2) Using a Rotation System Model. 3) Using a Flexing System Model. 4) Using an Online Turnaround System Model. 5) Using a Self-Combination System Model. 6)  Using the Online Control System Model. Metode the delivery of blended learning material which is a perfect combination of face-to-face and also online, where during the Covid-19 Pandemic, it is known that there are many technologies that have undergone developments that greatly support the world of education in order to achieve success in learning. This blended learning method is also considered effective because it is to develop an innovation in the world of education in order to create optimal results.